2012
DOI: 10.1038/jp.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

Tin-mesoporphyrin in the treatment of refractory hyperbilirubinemia due to Rh incompatibility

Abstract: We describe the use of tin-mesoporphyrin (SnMP) in the treatment of an infant with Rh hemolytic disease. The infant's hyperbilirubinemia responded to phototherapy but every time the phototherapy was discontinued, the serum bilirubin rebounded and repeat phototherapy was necessary. A single intramuscular dose of SnMP on day 18 eliminated the need for further phototherapy and allowed us to discharge this infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Due to the blockade of heme metabolism and reduction of the free iron status of cells, metalloporphyrins might affect hemoproteins and other enzymes, including cytochrome P450 (78). Rosenfeld et al concluded that SnMP combined with phototherapy was superior to phototherapy alone in neonates with significant IHB due to hemolysis (79), consistent with the results of another study (80). The efficacy, toxicity, and long-term benefits of metalloporphyrins are not clear, and further studies are needed in this regard (24,78,81).…”
Section: Metalloporphyrinsmentioning
confidence: 57%
“…Due to the blockade of heme metabolism and reduction of the free iron status of cells, metalloporphyrins might affect hemoproteins and other enzymes, including cytochrome P450 (78). Rosenfeld et al concluded that SnMP combined with phototherapy was superior to phototherapy alone in neonates with significant IHB due to hemolysis (79), consistent with the results of another study (80). The efficacy, toxicity, and long-term benefits of metalloporphyrins are not clear, and further studies are needed in this regard (24,78,81).…”
Section: Metalloporphyrinsmentioning
confidence: 57%
“…Rather, a prolonged sustained low level of bilirubin was observed, similar to the animal study [ 15 ], although still significantly lower than the control group [ 35 , 37 ]. This inferred that the profound inhibitory effect of Sn-MP is only evident by 24 to 48 hours with the initial sharp decline [ 38 ], but significant difference in bilirubin levels compared to the control group occurs only at three to five days posttreatment. Hence, further study with intravenous administration is also required to avoid the confounding effect of the route of administration in finding the exact efficacy of Sn-MP.…”
Section: Discussionmentioning
confidence: 99%
“…Reports with safety concerns Drummond et al [18] Hintz et al [23] Drummond and Kappas [19] DeSandre et al [20] Fort and Gold [24] Morioka et al [21] Wong et al [22] Vreman et al [25] Rosenfeld et al [35] Rosenfeld et al [36] Bhutani et al [37] Maisels and Yang [38] Valaes et al [39] Kappas et al [40] Martinez et al [41] Valaes et al [42] Kappas et al [43] Case reports: Kappas et al [32] Rubaltelli et al [33] Galbraith et al [34] Maisels and Yang [38]…”
Section: Reports Favoring Efficacymentioning
confidence: 99%
“…The Zn-protoporphyrin-lipid treatment has also been found to be effective in inhibition of hemoxygenase and reduction of hyperbilirubinemia in newborn mouse models [73]. The combination of phototherapy and SnMP also effectively reduced the duration and need of repeated phototherapy for the treatment of hyperbilirubinemia in infants with hemolytic disease due to Rh incompatibility [74].…”
Section: Recent Advancements In the Treatment Of Hyperbilirubinemiamentioning
confidence: 99%